MODEL INKUIRI TERBIMBING DENGAN DUKUNGAN ANIMASI 3D SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Luszia Asanti; An Nuril Maulida Fauziah (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study was motivated by the low level of students' critical thinking skills in science learning, particularly on the topic of the human respiratory system, which is abstract in nature, as well as the lack of active student engagement in the learning process. This study aims to determine the improvement of students' critical thinking skills, the implementation of learning, and students’ responses to the implementation of a guided inquiry learning model assisted by 3D animation. This research employed a quantitative approach with a pre-experimental design in the form of a one-group pre-test post-test. The subjects of this study were 27 students of class VIII D at MTs Negeri 4 Surabaya. Data were collected through tests (pre-test and post-test), observation sheets of learning implementation, and student response questionnaires. Data analysis was conducted using normality tests, paired sample t-tests, and N-Gain analysis. The results showed that there was an improvement in students' critical thinking skills, indicated by an increase in the average score from 46.67 to 67.04. The t-test results revealed a significant difference between pre-test and post-test scores (p < 0.05). The average N-Gain score was 0.37, categorized as moderate. In addition, the implementation of learning was categorized as very good, and students’ responses were also in the very good category. Therefore, it can be concluded that the implementation of the guided inquiry learning model assisted by 3D animation is effective in improving students' critical thinking skills.